Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Hotel Cosmo Amaroossa Jakarta - Jihan Nurfitria; Aden Prawiro Sudarso (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to evaluate the impact of Leadership Style (X1) and Physical Work Environment (X2) on Employee Performance at the Cosmo Amaroossa Hotel located in South Jakarta. The method used in this study is quantitative with an associative approach, which aims to assess the relationship between independent and dependent variables. The sampling technique applied is a saturated sampling technique, where data is obtained through observation and questionnaires from 60 participants. The results of the separate analysis show that the Leadership Style variable (X1) has an effect on Employee Performance (Y) with a regression equation of Y = 9.531 + 0.732 X1, and a correlation coefficient of 0.740, which indicates a strong relationship with a coefficient of determination of 54.8%. The results of the hypothesis test show that the calculated t is greater than the t table (4.243 > 2.000), so H0 is rejected and H1 is accepted, which means there is a significant influence between leadership style and Employee Performance. Other results show that the Physical Work Environment (X2) also influences Employee Performance (Y) with a regression equation of Y = 13.393 + 0.641 X2 and a correlation coefficient of 0.755, indicating a strong relationship with a determination coefficient of 56.9%. From the hypothesis test, the calculated t is greater than the t table (4.665 > 2.000), so H0 is rejected again and H2 is accepted, indicating a significant influence between the Physical Work Environment and Employee Performance. When viewed simultaneously, the variables Leadership Style (X1) and Physical Work Environment (X2) have a regression equation of Y = 6.974 + 0.424 X1 + 0.401 X2 with a correlation coefficient of 0.820 indicating a strong relationship and a determination coefficient of 67.3%, while 32.7% is influenced by other factors. The hypothesis test shows that the calculated F is greater than the F table (58.584 > 3.16), so H0 is rejected and H3 is accepted, which means that there is a significant simultaneous influence between Leadership Style and Physical Work Environment on Employee Performance at Cosmo Amaroossa South Jakarta.